Social Service Needs for Double-Misery Victims of Merapi Mountain Post-eruption - Siti Wahyu Iryani (Jurnal Penelitian Kesejahteraan Sosial, 2014)
As natural process which its intensity is more than normal, Merapi eruption disaster in Magelang Regency brings human victims, injuries, loss properties, social infrastructure, societal economic hinges, and refugees eruption impact. This research is done to describe double miseries and its social service needs of Merapi post eruption victims. This research uses survey method and implemented through qualitative-descriptive technique. The result shows that total human victims caused by Merapi post-eruption are 5006 people (1.891 family unit). They flee to five under districts and stay at emergency shelters. The disaster ruins 442 houses and 20.712 hectares of land. The victims suffer double miseries, form the eruption and post eruption impacts. The need for victims social services are medicines, health service, rehabilitation devices forbuildings, irrigation, forestry, communication, transportation, and land ownership management. It is recommended that local government, including lower level governmental management (desa, RW, RT) enable to mediate the distribution of aid and assistance because those institutions are the ones who know the local problem, condition, and needs of its environment.